DISPONIBILITY OF NITROGEN IN ECOLOGICAL HERBACEOUS EXTENSIVE CULTURES AND CONVENTIONAL: RELATIONSHIP WITH THE AMOUNT OF CARBON - Vera Avilés, Daniel (2012)
The availability of nitrogen in extensive herbaceous crops in the form of NO3-, NH4+ and PMN (potentially mineralizable nitrogen) in the area of Huesca (Spain) was determined. In conventional farming systems a greater contribution of nitrogen (N) is made than in the ecologic farming, but in these, on the other hand, the contribution of organic matter is much higher than conventional ones. The logical consequence would be to expect a higher content of N in soils from conventional farming, and increased organic matter content from soils with organic farming. However, the results of percentage of carbon (C) (representative of organic matter) obtained in this study did not corroborate the theory, because the main difference was found in the rainfed and irrigation management, regardless of whether it was conventional systems or ecological. The increased availability of nitrogen was found in soils with organic irrigation management.